Prejudice against Asian Immigrants in France - Zhang, Lijing (2018)
Guided by integrated threat theory, this study investigated the correlation of intergroup contact and the perception of threat from Asian immigrants in France. This study also took the potential effect of age, gender and education on the relationship between threat and contact into consideration. In contrast to hypothesis, results proved contact to be positively correlated with negative stereotypes, but negatively correlated with realist threat and symbolic threat. Education was proved to have no significant effect on the relationship between threat and contact, while age and gender was found to have significant influence on this relationship. Future research and potential limitation of this study are discussed.